2014
DOI: 10.1039/c4cy00027g
|View full text |Cite
|
Sign up to set email alerts
|

Deactivation studies of a carbon supported AuPt nanoparticulate catalyst in the liquid-phase aerobic oxidation of 1,2-propanediol

Abstract: The aerobic oxidation of 1,2-propanediol in alkaline aqueous solvent over bimetallic AuPt/C catalysts has been studied and catalyst reusability has been assessed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 39 publications
2
36
2
Order By: Relevance
“…FT‐IR spectra of the WH solid acids after five consecutive esterification/dehydration cycles (Supporting Information) show several differences on comparison with those of freshly prepared material. Covering of the surface by reaction products, as indicated by greater intensity C−H stretching vibrations in spent catalysts, is expected to lead to further reduced surface area, pore diameter, and pore volume, as indicated through prior work by D′Agostino and co‐workers …”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…FT‐IR spectra of the WH solid acids after five consecutive esterification/dehydration cycles (Supporting Information) show several differences on comparison with those of freshly prepared material. Covering of the surface by reaction products, as indicated by greater intensity C−H stretching vibrations in spent catalysts, is expected to lead to further reduced surface area, pore diameter, and pore volume, as indicated through prior work by D′Agostino and co‐workers …”
Section: Resultsmentioning
confidence: 94%
“…Covering of the surface by reaction products, as indicatedb yg reater intensity CÀHs tretching vibrations in spent catalysts, is expected to lead to furtherr educed surfacea rea, pore diameter,a nd pore volume, as indicated throughp rior work by D'Agostino and co-workers. [32] The deactivation or reduced catalytic performance of WH-PTSA catalysts on prolonged use can be explained based on FTIR data, as the result of active site contamination and some leaching of acidic sulfonate/sulfonic species. Decreasesi n -SO 3 Hv ibrationi ntensities( 1034cm À1 and 1160 cm À1 )r elative to fresh WH solid acids ( Figure 2D)s uggest leaching of, or gradualp oisoning of, these sites by water,w ith hydration of the catalysts urfaceb eing evident through enhanced broaden- ing of the O-H stretching vibration in reused catalystm aterials.…”
Section: Solid Acid Catalyst Reusability Profilesmentioning
confidence: 99%
“…Recently, some NMR‐based morphological studies of regular and irregular monolithic structures have been reported . Grosse et al investigated the porosity, pore size distribution, and other properties of heterogeneous structures.…”
Section: Introductionmentioning
confidence: 99%
“…NMR of thermally polarized gases is more challenging in comparison with that of liquids, due to reduced spin density, faster movements of the molecules, and the short transversal relaxation time T 2 , which cause a considerably reduced signal‐to‐noise ratio (SNR) in gas phase NMR , , . As a solution, studies on hyperpolarized gases have been published .…”
Section: Introductionmentioning
confidence: 99%
“…2,3 There are two lactic acid production processes, namely microbial fermentation and chemical synthesis. 6 Recently, selective catalytic oxidation of 1,2-propanediol has been considered as a green chemical route for lactic acid synthesis, 5,[7][8][9][10][11][12][13][14][15][16] which is due to the high lactic acid selectivity obtained in the catalytic oxidation of renewable 1,2-propanediol under mild reaction conditions. 4 However, the production of lactic acid by microbial fermentation is limited by the substrate and operating cost.…”
Section: Introductionmentioning
confidence: 99%